Magnetometric detection of explosive objects: opportunities and prospects - Orlyuk, M.I.; Kuznetsov, S.M.; Romenets, A.O.; Marchenko, A.V.; Orlyuk, I.M. (Geofizicheskiy Zhurnal, 2025)
One of the modern methods of mapping territories, including those contaminated with explosive ordnance (EOD), is remote magnetic surveying using UAVs. The method is based on the use of modern magnetometers and gradiometers, in particular LEMI-026, which, in combination with UAVs, record the components of the magnetic field. According to the results of experimental studies at landfills, it allows identifying accumulations of various metal residues, including explosive objects.